Human mesenchymal stem cells induced to differentiate as chondrocytes follow a biphasic pattern of extracellular matrix production. Issue 6 (22nd December 2017) - Sorrell, J. Michael; Somoza, Rodrigo A.; Caplan, Arnold I.
ABSTRACT: Regenerative medicine and tissue engineering studies are actively developing novel means to repair adult articular cartilage defects using biological approaches. One such approach is the harnessing of adult human therapeutic cells such as those referred to as mesenchymal stem cells. Upon exposure to chondrogenic signals, these cells differentiate and initiate the production of a complex and voluminous cartilaginous matrix that is crucial to both the structure and function of cartilage. Furthermore, this complexity requires the time‐sensitive activation of a large number of genes to produce the components of this matrix. The current study analyzed the kinetics of matrix production in an aggregate culture model where adult human mesenchymal stem cells were induced to differentiate as chondrocytes. The results indicate the existence of a biphasic mode of differentiation and maturation during which matrix genes and molecules are differentially activated and secreted. These results have important implications for developing novel approaches for the creation of tissue engineered articular cartilage. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1757–1766, 2018. Abstract : Human mesenchymal stem cells in aggregate culture form chondrogenic cells in a two‐stage differentiation process. Pre‐chondrogenic cells develop prior to day 3 in culture and mature chondrocytes develop between day 10 and day 14 in culture. Chondrogenic differentiation is demonstrated by a significant upregulation in mRNAs for multiple matrix molecules and this indicates a window for modulating chondrogenesis. The fold change data represent averages of two donors. See Supplemental Data section for more details.